The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1049/iet-wss.2013.0100
|View full text |Cite
|
Sign up to set email alerts
|

Improved adaptive localisation approach for indoor positioning by using environmental thresholds with wireless sensor nodes

Abstract: Jennic type wireless sensor nodes (WSN) are utilised together with environmentally adaptive localisation algorithm (EAL), to determine the unknown target positions. Received signal strength indicator (RSSI) values are employed within their standard deviation boundaries around their mean. Static standard deviation threshold concept for RSSI values is introduced to adapt them to environmental ranging factors. Trigonometric techniques are utilised together with EAL algorithm to calculate the unknown target positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The experimental results showed that the RSS data become smoother and less fluctuant by using the proposed averaging method. A more complex algorithm is proposed in [20] to further reduce the variation of RSS data by using a weighing method. This algorithm can greatly reduce the variation of RSS data, but the increase on computational complexity cannot be neglected.…”
Section: Rss Data Processing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental results showed that the RSS data become smoother and less fluctuant by using the proposed averaging method. A more complex algorithm is proposed in [20] to further reduce the variation of RSS data by using a weighing method. This algorithm can greatly reduce the variation of RSS data, but the increase on computational complexity cannot be neglected.…”
Section: Rss Data Processing Methodsmentioning
confidence: 99%
“…Trigonometric techniques are utilised together with EAL algorithm to calculate the unknown target positions in [20]. In EAL algorithm, the anchor node whose transmitted signal has minimum RSS value is taken as reference point.…”
Section: Location Estimation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their method employs a spring model to correct the positioning error by collaboratively adjusting the estimated positions. Koyuncu and Yang (2015) proposed a localization method that utilizes a static standard deviation threshold to adapt the environmental ranging factors. Their method also uses trigonometry to calculate the unknown target positions.…”
Section: Related Workmentioning
confidence: 99%
“…Many costeffective solutions have been developed for indoor location estimation in recent years. Indoor positioning systems using received signal strength emerged as low-cost systems achieving acceptable accuracy for many applications [2,3]. Ultra-wideband (UWB) technology [4] has also appeared for accurate and precision indoor location estimation.…”
Section: Introductionmentioning
confidence: 99%